Difference between revisions of "Torsion is tensorial"

From Diffgeom
Jump to: navigation, search
(Proof)
Line 4: Line 4:
 
===Symbolic statement===
 
===Symbolic statement===
  
Let <math>M</math> be a [[differential manifold]] and <math>\nabla</math> be a [[linear connection]] on <math>M</math> (viz., <math>\nabla</math> is a [[connection]] on the [[tangent bundle]] <math>TM</math> of <math>M</math>).
+
Let <math>M</math> be a [[differential manifold]] and <math>\nabla</math> be a [[fact about::linear connection]] on <math>M</math> (viz., <math>\nabla</math> is a [[connection]] on the [[tangent bundle]] <math>TM</math> of <math>M</math>).
  
Consider the [[torsion of a linear connection|torsion]] of <math>\nabla</math>, namely:
+
Consider the [[fact about::torsion of a linear connection|torsion]] of <math>\nabla</math>, namely:
  
 
<math>\tau(\nabla): \Gamma(TM) \times \Gamma(TM) \to \Gamma(TM)</math>
 
<math>\tau(\nabla): \Gamma(TM) \times \Gamma(TM) \to \Gamma(TM)</math>
Line 14: Line 14:
 
<math>\tau(\nabla)(X,Y) = \nabla_X Y - \nabla_Y X - [X,Y]</math>
 
<math>\tau(\nabla)(X,Y) = \nabla_X Y - \nabla_Y X - [X,Y]</math>
  
Then, <math>\tau(\nabla)</math> is a [[tensorial map]] in both coordinates.
+
Then, <math>\tau(\nabla)</math> is a [[fact about::tensorial map]] in both coordinates.
  
 
==Facts used==
 
==Facts used==

Revision as of 01:19, 24 July 2009

This article gives the statement, and possibly proof, that a map constructed in a certain way is tensorial
View other such statements

Statement

Symbolic statement

Let M be a differential manifold and \nabla be a linear connection on M (viz., \nabla is a connection on the tangent bundle TM of M).

Consider the torsion of \nabla, namely:

\tau(\nabla): \Gamma(TM) \times \Gamma(TM) \to \Gamma(TM)

given by:

\tau(\nabla)(X,Y) = \nabla_X Y - \nabla_Y X - [X,Y]

Then, \tau(\nabla) is a tensorial map in both coordinates.

Facts used

\! X(fg) = (Xf)(g) + f(Xg)

\! f[X,Y] = [fX,Y] + (Yf)X

\! f[X,Y] = [X,fY] - (Xf)Y

  • The Leibniz rule axiom that's part of the definition of a connection, namely:

\! \nabla_X(fZ) = (Xf)(Z) + f\nabla_X(Z)

Proof

Tensoriality in the first coordinate

We'll use the fact that tensoriality is equivalent to C^\infty-linearity.

To prove: \tau(\nabla)(fX,Y) = f\tau(\nabla)(X,Y)

Proof: We prove this by expanding everything out on the left side:

\tau(\nabla)(fX,Y) = \nabla_{fX}(Y) - \nabla_Y(fX) - [fX,Y] = f \nabla_X Y  - f \nabla_Y X - (Yf)(X) - [fX,Y]

To prove the equality with f \tau(\nabla)(X,Y), we observe that it reduces to showing:

\! (Yf)(X) = f[X,Y] - [fX,Y]

which is exactly what the corollary of Leibniz rule above states.

Tensoriality in the second coordinate

The proof is analogous to that for the first coordinate.

To prove \tau(\nabla)(X,fY) = f \tau(\nabla)(X,Y)

Proof: We prove this by expanding everything out on the left side:

\tau(\nabla)(X,fY) = \nabla_X(fY) = \nabla_{fY}(X) - [X,fY] = (Xf)(Y) + f \nabla_XY - f\nabla_YX - f[X,Y] - (Xf)Y

(the last step uses the corollary of Leibniz rule).

Canceling terms, yields the required result.